Don’t Go Alone: Pentingnya Menggalang Kolaborasi Stratejik Pemerintah Daerah dan DPRD sebagai Langkah Mewujudkan Tujuan Desentralisasi - Faozan, Haris (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
Local government and local legislature are equal partners in conducting local governance. This mutual relationship supposed to be a strategic collaboration. In fact, there are a lot of obstacles between their relations; they have different perspective in understanding their role and tasks. For example in making local law and budgeting, local government and local legislature seem stand in opposite sides. These differences lead to chaotic problems and become a cause pf development stagnation. Strategic collaboration can be a method for local government capability. Through this method, local governance can make freat difference in their performance